Stress and your health : from vulnerability to resilience - Anisman, Hymie (Hoboken : Wiley-Blackwell, 2015)
'Stress and Your Health: From Vulnerability to Resilience presents an evidence-based evaluation of the various effects of stress, along with methods to alleviate distress and stress-related illnesses. Examines myriad stressor effects and proven ways to alleviate stress in our lives Covers a wide range of stressor-related topics including therapeutic strategies to deal with stress and factors that hinder treatment of stress Makes difficult biochemical and immunological concepts accessible to a non-specialist audience Addresses many of the factors that cause individuals to be more vulnerable to the impact of stressors and at increased risk for pathology'--
'Covers a wide range of stressor-related topics including therapeutic strategies to deal with stress and factors that hinder treatment of stress'--
Machine generated contents note: What this book is about -- What do we mean when we talk about stressors? -- The characteristics of stressors: comparing apples, oranges, and lemons -- Chronic stressors and allostatic overload -- Before you go ... -- Vulnerability and resilience -- Genetic influences -- Age -- Sex -- Personality differences in relation to stress responses -- Previous stressor experiences -- Stress generation -- Before you go ... -- Appraising stressors -- Guidance through primary and secondary appraisals -- Thinking fast and slow -- Guideposts and anchors -- Appraisals based on what others think -- Appraisals in relation to learning, memory, automaticity, expectation, and habit -- Positive and negative emotions -- Gauging stressors -- Before you go ... -- First responses to stressors -- Coping methods -- Personal growth and finding meaning -- Social support -- Loneliness -- Unsupportive interactions -- Social rejection -- Forgiveness and trust -- Empathy -- Before you go ... -- What's a hormone? -- Linking hormones and behaviors -- The hormonal stress response -- Hormones of the autonomic nervous system -- The hypothalamic-pituitary-adrenal (HPA) axis and glucocorticoids -- What cortisol (corticosterone) does for us -- The cortisol/corticosterone response to an acute stressor -- Cortisol variations in humans -- Yesterday's stressors influence today's responses -- A cacophony of hormones associated with stress, eating and energy regulation: leptin, ghrelin, CRH, and neuropeptide Y -- Oxytocin and positive responses -- Estrogen and testosterone -- Before you go ... -- Neuronal and glial processes in relation to challenges -- Stressors influence neurotransmitter functioning -- Acetylcholine (ACh) -- Serotonin, norepinephrine and dopamine -- Corticotropin releasing hormone (CRH): beyond the HPA system -- Glutamate -- Gamma-aminobutyric acid (GABA) -- Cannabinoids -- Neurotrophic factors -- The past influences the future -- Before you go ... -- A brief look at how the immune system works -- Cells of the immune system -- Immune memories -- Cytokines: messenger molecules of the immune system -- Immune[--]hormone interactions -- Stress, brain processes, and immunological changes -- Cytokine changes in response to stressors -- Before you go ... -- Connections over time -- Prenatal experiences -- Biological correlates of prenatal stress in humans -- Consequences of prenatal infection in animals and humans -- Stress experienced early in life -- Transitional periods -- Older age -- Before you go ... -- Coronary artery disease (CAD) -- The heart's response to a challenge -- Psychosocial factors associated with heart disease -- The influence of stressors on heart disease -- Job strain -- Depressive illness and heart disease -- Socioeconomic status (SES) -- Sex-dependent trajectories for heart disease -- Personality factors and heart disease -- Type A personality -- Type D personality -- Physiological stress responses associated with heart disease -- Sympathetic nervous system reactivity -- Inflammatory processes in heart disease -- Stress, pathogen burden, and heart disease -- Obesity, cytokines, and heart disease -- Before you go ... -- Type 1 diabetes -- Type 2 diabetes -- Stressor influences in relation to the development of Type 2 diabetes -- Immune factors in Type 2 diabetes -- Genetic contributions -- Before you go ... -- Immunity and illness -- Allergies -- Infectious illness -- Stressors influence vulnerability and the course of infectious illness -- Autoimmune disorders -- Exacerbation of autoimmune disorders by stressful experiences -- Before you go ... -- The cancer process -- The stress[--]cancer link -- Implication for cancer treatment -- Stress stemming from cancer -- Treating cancer-related distress -- Before you go ... -- What is depression? -- Depressive subtypes -- Cognitive theories of depressive disorders -- Helplessness -- Hopelessness -- Depression from an evolutionary perspective -- Depression from a neurochemical vantage -- Neurobiological explanations of depressive disorders -- Serotonin, norepinephrine and dopamine in relation to depressive disorders -- Gene and environmental interactions -- Reward processes in depression: dopamine and anhedonia -- Depression and anxiety: corticotropin releasing hormone (CRH) as a player in depression -- Coordination and discoordination of neuronal process: gamma-aminobutyric acid (GABA) -- Growth factors and depression -- Inflammatory processes and depressive disorders -- Before you go ... -- A plague of anxiety disorders -- Generalized anxiety disorder (GAD) -- Panic disorder -- Obsessive-compulsive disorder (OCD) -- Phobias and social anxiety -- Before you go ... -- Acute stress disorder -- Posttraumatic stress disorder -- Vulnerability and resilience -- Neuroanatomical underpinnings of PTSD -- Biochemical determinants of PTSD -- CRH and corticoids in relation to PTSD-related memories -- Norepinephrine and serotonin and PTSD-related memories -- GABA and the extinction of fear responses in PTSD -- Neuropeptide Y (NPY) and resilience -- Before you go ... -- What's an addiction -- Stress as a provocateur in the addiction process -- Reward and aversion in relation to addiction: a multistep process -- Dopamine in relation to stress and reward -- Corticotropin hormone in relation to stress and addiction -- Can eating become an addiction? -- An integrated perspective -- Treatment for addictions -- Before you go ... -- How might illness come to affect health? -- Major physical illnesses -- What patients know and what they need to know -- Appraising and coping with illness -- Personal control, decision-making, and trust -- Social support and unsupportive interactions in the face of illness -- Mood changes associated with illness -- Adjustment to chronic illnesses: psychological resilience in the face of illness -- Stress associated with caregiving -- Loss and grief -- Before you go ... -- Job-related distress -- Status and job strain -- Burnout -- Absenteeism and presenteeism -- Bullying in the workplace -- Social support in the workplace -- Trust in the workplace -- Unemployment -- Time management and juggling -- Before you go ... -- Traveling across generations -- Parental stress influences on children -- Intergenerational effects of trauma: beyond poor parenting -- Environments modify gene actions -- The case of epigenetic effects -- Collective and historic trauma -- Before you go ... -- Prelude to dealing with stress -- Relaxation training -- Exposure therapy -- Cognitive behavioral therapy (CBT) -- Interpersonal psychotherapy (IPT) -- Meditation -- Mindfulness -- The default mode network -- Positive psychotherapy (PPT) -- Giving and receiving -- The social cure -- Before you go ... -- Something about drug treatments -- Placebo and nocebo responses -- Selecting the right treatment and related caveats -- Treating depression -- Selective serotonin reuptake inhibitors (SSRIs) -- A cocktail of acronyms: SNRI, NDRI, NaSSA, MAOI -- Ketamine -- Deep brain stimulation -- Anti-inflammatory agents -- Treating anxiety disorders -- Treating PTSD -- Herbal (naturopatbic) treatments -- Before you go ... -- It's OK to go now ...
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Stress (Psychology); Health; Psychophysiology; PSYCHOLOGY -- Mental Health; Health; Psychophysiology; Stress (Psychology); Electronic books